ANALISA PEMBELAJARAN AKSARA BALI BERBASIS AUGMENTED REALITY MENGGUNAKAN MODEL KANO DAN MODEL USE QUESTIONNAIRE - Gerson Feoh; Christian Tonyjanto; Rheza Paleva Wiryadikara (LPPM Universitas Dhyana Pura, 2019)
ABSTRACTThis study aims to analyze the implementation of Augmented Reality (AR-Learning) in the learning of Balinese Script in elementary school age students. The Balinese script as one of the regional scripts that has become one of the regional writings to be introduced compulsorily to school children from elementary school through high school in the province of Bali. The conventional learning model introducing Balinese Script is often unsuccessful due to the lack of interesting process of introducing and learning the Balinese Script. For this reason, alternative learning methods using technology can be implemented, one of which uses Augmented Reality, or better known as AR-Learning. By utilizing Android-based smartphones, learning Balinese script will certainly be more fun for elementary school students. In this study, students of grade 3 SDN 1 B.B Agung used a case study in this research.The results of this study are the Balinese Augmented Reality card complete with an analysis of Android-based Balinese learning implementation with Augmented Reality technology using the Kano Model to categorize the attributes of AR-Learning user satisfaction and the USE Questionnaire Model for evaluation of usability recommendations for applications based on 4 quality dimensions namely the dimensions of usefulness, ease of use, ease of learning, and satisfaction.Keywords: Balinese Script, Augmented Reality, Extent of Satisfaction, Extent of Dissatisfaction, Canoe Model.ABSTRAKPenelitian ini bertujuan untuk menganalisis impelementasi Augmented Reality (AR-Learning) dalam pembelajaran Aksara Bali pada siswa usia sekolah dasar. Aksara Bali sebagai salah satu aksara daerah yang sampai saat ini menjadi salah satu tulisan daerah yang wajib diperkenalkan kepada anak-anak sekolah mulai usia Sekolah Dasar sampai dengan Sekolah Menengah Atas di Provinsi Bali. Model pembelajaran konvensional mengenalkan Aksara Bali seringkali tidak berhasil karena kurang menariknya proses pengenalan dan pembelajaran Aksara Bali tersebut. Untuk itu, diperlukan metode pembelajaran yang memanfaatkan teknologi dalam pembelajaran, salah satu nya menggunakan Augmented Reality, atau lebih dikenal dengan AR-Learning. Dengan memanfaatkan smartphone berbasis Android, pembelajaran Aksara Bali tentunya akan lebih menyenangkan siswa-siswi Sekolah Dasar. Dalam peneliitian siswa-siswi kelas 3 SDN 1 B.B Agung digunakan studi kasus dalam penelitian ini.Hasil dari penelitian ini adalah kartu Augmented Reality Aksara Bali lengkap dengan analisa implementasi pembelajaran Aksara Bali berbasis Android dengan teknologi Augmented Reality menggunakan Model Kano untuk mengkategorikan atribut-atribut kepuasan pengguna AR-Learning dan Model USE Questionnaire untuk evaluasi usabilitas rekomendasi terhadap aplikasi berdasarkan 4 dimensi kualitas yaitu dimensi usefulness, ease of use, ease of learning, dan satisfaction.Kata Kunci: Aksara Bali, Augmented Reality, Extent Of Satisfaction, Extent Of Dissatisfaction, Kano Model.